Understanding policy making and policy implementation with reference to land redistribution in South Africa : case studies form the Eastern Cape - Mbokazi, Nonzuzo Nomfundo Mbalenhle (Rhodes University, Faculty of Humanities, Department of Sociology, 2015)
This thesis focuses on land reform in post-apartheid South Africa and specifically on land redistribution, as one of the main pillars of land reform. There have been many studies undertaken on land redistribution in South Africa and these studies offer deep criticisms of the prevailing land redistribution model (a market-led, but state-assisted model) and the ways in which this model has failed to meaningfully address colonial dispossession of land. Further, studies have focused on post-redistribution livelihoods of farmers and the many challenges they face. One significant gap in the prevailing literature is a sustained focus on the state itself, and particularly questions around policy formation and implementation processes pertaining to land redistribution. Delving into policy processes is invariably a difficult task because outsider access to intra-state processes is fraught with problems. But a full account of land redistribution in South Africa demands sensitivity to processes internal to the state. Because of this, it is hoped that this thesis makes a contribution to the existing South African land redistribution literature. In pursuing the thesis objective, I undertook research amongst farmers on selected redistributed farms outside Grahamstown in the Eastern Cape, as well as engaging with both current and former state land officials. Based on the evidence, it is clear that the policy process around land in South Africa is a complex and convoluted process marked not only by consensus-making and combined activities but also by tensions and conflicts. This, I would argue, is the norm with regard to what states do and how they work.
Keywords: Land reform -- South Africa -- Eastern Cape; Land reform -- Law and legislation -- South Africa; Land reform -- Case studies; Agriculture and state -- South Africa; South Africa -- Economic conditions -- 1918-1961; South Africa -- Economic conditions -- 1961-1991; South Africa -- Economic conditions -- 1991-; Reconstruction and Development Programme (South Africa)